2008
DOI: 10.1007/s11538-008-9348-8
|View full text |Cite
|
Sign up to set email alerts
|

Persistence and Spread of Gastro-Intestinal Infections: the Case of Enterotoxigenic Escherichia coli in Piglets

Abstract: Several gastro-intestinal infections in animal husbandry not only greatly reduce the well-being of animals, but also have the potential to cause large economical damage. Understanding of the dynamics of such diseases is thus of great importance. In this paper, we focus on within-host dynamics and present a model describing the dynamics of pathogens in the intestine of a single host. Our motivation to study the problem stems from the case of enterotoxigenic Escherichia coli in newly weaned piglets, but the mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…Previous studies have confirmed that the E. coli F18 strain is the main pathogen responsible for porcine post-weaning diarrhea (PWD) [11]. Via its fimbriae, ETEC F18 pathogen adheres to the surface of epithelial cells of the small intestines of piglets and binds to specific receptors in the brush border membrane host intestinal mucosa, leading to colonization, replication and production of enterotoxin and lipopolysaccharide (LPS) [12].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have confirmed that the E. coli F18 strain is the main pathogen responsible for porcine post-weaning diarrhea (PWD) [11]. Via its fimbriae, ETEC F18 pathogen adheres to the surface of epithelial cells of the small intestines of piglets and binds to specific receptors in the brush border membrane host intestinal mucosa, leading to colonization, replication and production of enterotoxin and lipopolysaccharide (LPS) [12].…”
Section: Introductionmentioning
confidence: 99%
“…These diseases are responsible for tremendous damage and economic losses in the pig industry [1]. Some molecular genetic studies by both national and international researchers have investigated the factors determining immunological resistance of pigs to ETEC F18.…”
Section: Introductionmentioning
confidence: 99%
“…Although this describes the system for which the model was originally developed (the mammalian gut) relatively well, it appears too simplistic for biofilm systems, where the wall attached bacteria can grow in thick layers in which concentration gradients can develop, and where the colonization surface is not limiting the capacity for wall attachment. A greatly simplified version of the Freter model has been used for description and analysis of gastro-intestinal E coli infections [7]. In this study we revisit the Freter model for a CSTR.…”
Section: Introductionmentioning
confidence: 99%